Applications of Biophysics in High-Throughput Screening Hit Validation. (June 2014) - Genick, Christine Clougherty; Barlier, Danielle; Monna, Dominique; Brunner, Reto; Bé, Céline; Scheufler, Clemens; Ottl, Johannes
For approximately a decade, biophysical methods have been used to validate positive hits selected from high-throughput screening (HTS) campaigns with the goal to verify binding interactions using label-free assays. By applying label-free readouts, screen artifacts created by compound interference and fluorescence are discovered, enabling further characterization of the hits for their target specificity and selectivity. The use of several biophysical methods to extract this type of high-content information is required to prevent the promotion of false positives to the next level of hit validation and to select the best candidates for further chemical optimization. The typical technologies applied in this arena include dynamic light scattering, turbidometry, resonance waveguide, surface plasmon resonance, differential scanning fluorimetry, mass spectrometry, and others. Each technology can provide different types of information to enable the characterization of the binding interaction. Thus, these technologies can be incorporated in a hit-validation strategy not only according to the profile of chemical matter that is desired by the medicinal chemists, but also in a manner that is in agreement with the target protein's amenability to the screening format. Here, we present the results of screening strategies using biophysics with the objective to evaluate the approaches, discuss the advantages and challenges, and summarize the benefits in reference to lead discovery. In summary, the biophysics screens presented here demonstrated various hit rates from a list of 2000 preselected, IC50 -validated hits from HTS (an IC50 is the inhibitor concentration at which 50% inhibition of activity is observed). There are several lessons learned from these biophysical screens, which will be discussed in this article.